2011
DOI: 10.1111/j.1442-200x.2010.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Ponseti management of clubfoot after walking age

Abstract: The Ponseti method is effective in correcting deformities of clubfoot, even after walking age, but affectivity may decrease with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…It is clear that this improvement supplies a much better basis for the surgery even when it is not sufficient to achieve a fully corrected foot. We agree with the statement of Yagmurlu et al [20] that whatever the presenting age of the patient with club foot, the Ponseti method should be applied, at least to achieve some improvement of the deformity. However, it follows from our results that it is impossible to cure all club feet with …”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…It is clear that this improvement supplies a much better basis for the surgery even when it is not sufficient to achieve a fully corrected foot. We agree with the statement of Yagmurlu et al [20] that whatever the presenting age of the patient with club foot, the Ponseti method should be applied, at least to achieve some improvement of the deformity. However, it follows from our results that it is impossible to cure all club feet with …”
Section: Discussionmentioning
confidence: 43%
“…There are a lot of studies reporting that recurrence after correction is related to patients' compliance with bracing [19,20]. When the parents of patients do not comply with the bracing protocol, many major and minor recurrences should be expected.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has been shown to predict the need for Achilles tenotomy 102 and is emerging as a popular outcome measure in studies of older children with relapsed clubfoot ( Figure 11). 11,82,85,130,131 Predictive capacity for longer term outcomes are conflicting. One study found the Dimeglio Scale at birth to be a poor predictor of quality of gait at 2 year follow-up, 82 while another study reported a good correlation with outcome at two years.…”
Section: The Dimeglio Scalementioning
confidence: 99%
“…Manipulation time is increased, lesser foot abduction and dorsiflexion are acceptable, knee flexion in an above knee cast is decreased, cast duration is extended, different casting material is proposed, increased cast duration post tenotomy for tendo Achilles healing and an altered brace regime is suggested ( Table 1). The surgical intervention has increased beyond percutaneous tenotomy with open Achilles tendon lengthening and posterior release added as modifications of the Ponseti technique in older children [4,9]. Some series recommend an additional split tibialis anterior transfer at the time of equinus correction to tide over the brace compliance problem, while others do not recommend it [3].…”
mentioning
confidence: 99%
“…The Ponseti method has found most use in developing countries where late presentation of clubfoot is also fairly common. Several papers now routinely recommend this technique up to two years of age and depict success rates almost equivalent to infants [2][3][4][5][6][7][8][9]. We would like to broaden the review to include clubfoot treatment by Ponseti method in older children with late presentation and raise some issues related to this extended use.…”
mentioning
confidence: 99%